DEVELOPING STUDENTSÃ¢â¬â¢ RETELLING STORY ABILITY THROUGH COLLABORATIVE LEARNING TECHNIQUES - Farida, Diana (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
The ability of speaking English has become very important in this global era. To facilitate junior high school students to gain the competence, English teachers employ various techniques to reach the goal with the curriculum as the guideline. The research was conducted by employing two Collaborative Learning (CL) techniques Ã¢â¬â Think Team Share and Chain Work.ÃÂ The objectives of this study are (1) to investigate to what extent CL can enhance the ability of the VIII A students of SMPN 2 Semarang to retell stories and (2) to investigate that CL can develop manner of the VIII A students of SMPN 2 Semarang to retell stories. The research was conducted through Action Research with two cycles. Each cycle consists of planning, acting, observing and reflecting. The results of the research can be concluded as follows: (1) CL techniques implemented during the research Ã¢â¬â Think Team Share and Chain Work Ã¢â¬â had successfully developed studentsÃ¢â¬â¢ retelling story ability. Before the research, studentsÃ¢â¬â¢ speaking average score is 72.26, and at the end of the research it is 82.30. The score has exceeded the speaking passing grade, 76. Before the research, 69% of the students gained the passing grade, while - at the end of the research- 88%. This proved that the two techniques had developed studentsÃ¢â¬â¢ retelling story ability to the extent of 19%. (2) Based on the second requirement of the research, the two CL techniques could not successfully develop studentsÃ¢â¬â¢ manner in retelling stories to 85%. Before the research there are 16 (62%) students who could retell stories in appropriate manners, while Ã¢â¬â at the end of the research Ã¢â¬â there are 20 (77%) who could do so. ÃÂ Key Words: retelling story ability, collaborative learning techniques